Overlaid temporomandibular joint disorders and otology symptoms – A diagnostic approach and management considerations for otolaryngologists and dentists - Santosh, Vasavi; Hinduja, Shweta; Manoj, Reema; Waghmare, Mandavi (Eastern Journal of Medical Sciences, 2020)
There is an overlap of symptoms related to temporomandibular joint disorders (TMD) and otological diseases. It becomes empirical to differentiate the two conditions since the prevalence of otalgia, tinnitus, headache, etc., in TMD patients may be as high as 50%. This review paper discusses the overlapping symptoms, diagnostic work up and treatment strategies for TMD, aiding both the oral physician and otolaryngologist to be able to treat the patient in a holistic manner.